IMPROVING TEACHER MOTIVATION THROUGH THE USE OF TEACHING TOOLS WITH DIRECT LEARNING - Sudarmiatun (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to determine whether using teaching aids in direct learning can increase the teaching motivation of teachers at SMP Negeri 1 Bangko, Rokan Hilir Regency. This research is only limited to increasing teacher motivation in teaching by using teaching aids at SMP Negeri 1 Bangko, Rokan Hilir Regency. The research subjects consisted of 23 teachers. Based on the results of the analysis and discussion, it can be concluded that the aspect of the principal's activity as a facilitator is achieved with a score of 25 or with a percentage of 63 from all aspects of the assessment or by 63% of all activities are achieved. Then in the second cycle, the score obtained was 38 or with a percentage of 95% of all aspects achieved. In the aspect of teacher activity as a participant in this study, in the first cycle, the score obtained from the implementation of the direction by the principal got a score of 52 or with a percentage of achievement of 28%. Then in cycle II, the participation rate was 76% higher than cycle I and with an implementation score of 80. In terms of teacher motivation during the implementation of the direction from cycle I to cycle II, teacher motivation in using teaching aids tended to increase. In the first cycle, the percentage of achievement was 64% in the good category, then the second cycle got a percentage of 82% or in the very good category.